1988
DOI: 10.4102/koedoe.v31i1.482
|View full text |Cite
|
Sign up to set email alerts
|

South African Acari. III. On the Mites of the Mountain Zebra National Park

Abstract: Ten new mite species are described and figured and new records of 19 mite species are given for the Mountain Zebra National Park. A check list is included

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The only previous record of this species is its original description (Meyer & Ueckermann 1988), in which the authors found it on Protasparagus laricinus (Burch.) in Mountain Zebra National Park, located in the Republic of South Africa, in 1986.…”
Section: *Tydeus Reticoxus Ueckermannmentioning
confidence: 99%
“…The only previous record of this species is its original description (Meyer & Ueckermann 1988), in which the authors found it on Protasparagus laricinus (Burch.) in Mountain Zebra National Park, located in the Republic of South Africa, in 1986.…”
Section: *Tydeus Reticoxus Ueckermannmentioning
confidence: 99%